Variation in Phenol Colour in Relation to Age of Rice Seeds - S.K. CHAKRABARTY,; K.C. NANDI,; MALAVIKA DADLANI, (Seed Research, 2026)
Identification of plant varieties, based on morphological, physiological or biochemical characteristics, is of great significance in variety development, protection, seed production and certification programmes. Keeping this in view, 49 released varieties of rice were tested and characterized on the basis of phenol colour reaction. Intra-varietal differences and the effect of physiological status of seed were determined in fresh and one year old seeds of all varieties. The study revealed that the above rice varieties could be grouped into five discrete colour groups by phenol test. However, 19 varieties out of 49 showed intra-varietal variation in the colour intensities, where as it was consistent in the remaining 30 varieties. The varieties exhibiting no colour change were most consistent with respect to phenol reaction with 100 per cent reproducibility. The intensity of the phenol colour reaction deepened with seed age in 14 out of 19 lots. Thus, it is concluded that phenol test may be performed on fresh seeds and the test should be used only to classify varieties as colour positive (light brown, brown, dark brown and black) and colour negative (no colour).